Micro-nano aggregate based on silanized calcium sulfate whisker in-situ polymerization and application
By using micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers in mountain tunnel construction, the durability of concrete in low temperature environment and freeze-thaw cycle is solved, and higher freezing resistance and water permeability are achieved, and the service life of concrete is extended.
Patent Information
- Application Number
- CN202411994724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
In the construction of mountain tunnels, the durability of concrete is affected by factors such as low temperature environment, freeze-thaw cycles and geological disasters, resulting in sharp reduction in strength and structural damage. It is difficult for the existing technology to effectively solve these problems.
Using micro-nano aggregates based on in-situ polymerization of silanized calcium sulfate whiskers, the nanosilicon dioxide is loaded onto the calcium sulfate whiskers and modified by silane coupling agent to form a three-dimensional network structure, which synergizes the strength and toughness of the material.
This technology significantly improves the anti-freeze, water permeability and sulfate corrosion resistance of concrete, extends the service life of concrete, and reduces the rebound rate of sprayed concrete.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of shotcrete admixtures, and in particular to a micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers and an application thereof. Background Art
[0002] As a representative construction project in my country, National Highway G318 faces many unique background factors that affect durability during tunnel construction in mountainous areas. The main tunnel of Zheduoshan Tunnel has complex geology, and the surrounding rock of the heading is mainly slate, which is strongly weathered. The rock mass is severely squeezed by the structure, and joints and fissures are developed. The rock mass is extremely broken and blocky. The groundwater is relatively developed and flows out of the rock cracks in strands. The rock mass becomes muddy when it meets water, and the surrounding rock loses its self-stabilizing ability. At the same time, some sections are located in the plate boundary zone or earthquake-active zone. During this period, the cave roof cracks, the surface leaks, the arch often collapses, and collapse cavities are formed. Geological disasters such as water gushing and large deformation of the primary support occur frequently. The cumulative time for geological disaster treatment has reached 20% of the total construction, seriously affecting the construction quality and progress.
[0003] Tunnels are plagued by water and mud, and long-term water penetration causes corrosion of internal steel bars and accelerated carbonization of concrete. In high-altitude areas, the temperature is extremely low, reaching tens of degrees below zero in winter. Frequent freeze-thaw cycles have become a key factor threatening the durability of concrete. The frost heave effect destroys the pore structure of concrete and sharply reduces its strength. Existing technical solutions improve the internal structure of concrete by adding air entraining agents, water reducers, rust inhibitors, etc., improve the concrete's impermeability, prevent the intrusion of external corrosive media, and extend the service life of concrete and steel bars. Nanofillers can effectively reduce the penetration of harmful substances in concrete by reducing pore connectivity and increasing the tortuosity of the transmission channel. CN111320411 provides a high-strength shotcrete admixture, which generates nanofillers by adding silica microspheres to micron-sized regenerated silk fibroin fibers. The nanofillers improve the strength of the concrete while optimizing the gradation of the cementitious material, and have stronger resistance to sulfate corrosion. However, under low temperature conditions, microstructural damage may occur inside the fibers, such as structural changes in the crystalline and non-crystalline regions, local breakage of the molecular chains, etc. The regenerated silk fibroin fibers lose flexibility and elasticity, and their ability to adsorb water is weakened, making it impossible for the support system to meet strength and durability indicators. Summary of the invention
[0004] The present invention provides a micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers and its application. Nano silicon dioxide (NS) is first loaded onto calcium sulfate whiskers (CSW), and then CSW / NS is modified by a silane coupling agent. The silanized CSW / NS can be dispersed relatively evenly between or on the surface of graphene oxide (GO) sheets. As the in-situ polymerization reaction proceeds, the GO sheets may overlap and stack with each other, and the silanized CSW / NS is interspersed therein. The functional groups are closely combined to form a three-dimensional network structure, which synergistically enhances the strength and toughness of the material, effectively transmits stress and hinders crack propagation in the support system.
[0005] Technical solution of the present invention A micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers, the main component of which is acrylic acid ester copolymer CSW / NS-GO, and the preparation method thereof comprises the following steps: (1) Nano-silicon dioxide is loaded on the surface of calcium sulfate whiskers; (2) Silanized modified calcium sulfate whiskers; (3) Preparation of graphene oxide by Hummers method; (4) Preparation of acrylate copolymer CSW / NS-GO by in situ polymerization.
[0006] Furthermore, the surface of the calcium sulfate whisker is loaded with nano-silicon dioxide specifically as follows: The sol-gel method is used to dissolve the silicon source in an organic solvent containing calcium sulfate whiskers, and an appropriate amount of water and an acidic catalyst are added. A hydrolysis reaction is carried out under stirring conditions to generate silicic acid and ethanol. The silicic acid undergoes a condensation reaction to generate nano-silica, which interacts with the surface of the calcium sulfate whiskers in the reaction system to obtain CSW / NS.
[0007] Furthermore, the silicon source is sodium silicate or ethyl orthosilicate.
[0008] Furthermore, the acidic catalyst provides hydrogen ions to accelerate the hydrolysis of TEOS, and is specifically one or more of tartaric acid, methanesulfonic acid, and p-toluenesulfonic acid.
[0009] As a preferred solution, while generating nano-silica, an epoxy silane coupling agent is added to participate in the formation process of nano-silica, and epoxy groups are introduced into the structure of nano-silica through a condensation reaction with silicic acid; on the other hand, its active functional groups can react with active sites such as hydroxyl groups on the surface of calcium sulfate whiskers, so that the generated epoxy-modified nano-silica is firmly supported on the calcium sulfate whiskers.
[0010] Furthermore, the epoxysilane coupling agent is specifically one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0011] Further, the silanized modified calcium sulfate whisker is specifically: A mixed solution of anhydrous ethanol and deionized water containing an aminosilane coupling agent is prepared, and the CSW / NS obtained in the previous step is added to the mixed solution, and ultrasonic treatment is performed for full reaction to obtain silanized CSW / NS. The ultrasonic action makes the calcium sulfate whiskers dispersed evenly, accelerates the hydrolysis reaction, and quickly forms reactive silanols. The microjets and shock waves generated by ultrasound can promote the collision frequency of silanols with hydroxyl groups on the surface of the calcium sulfate whiskers, accelerate the speed of the condensation reaction, and more amino groups are introduced into the surface of the calcium sulfate whiskers after ultrasonic treatment, and the distribution is more uniform, which makes the interface bonding between the whiskers and the base material more uniform and firm.
[0012] Furthermore, the aminosilane coupling agent is one or more of γ-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0013] Furthermore, the Hummers method for preparing graphene oxide specifically comprises the following steps: S11: In an ice bath, graphite powder is added to concentrated sulfuric acid, stirred evenly, and then sodium nitrate and potassium permanganate are added, the reaction temperature is controlled not to exceed 20° C., and stirring is continued to obtain a dark green mixture; S12: transferring the dark green mixture to a warm water bath, controlling the temperature not to exceed 50° C., and continuously stirring to obtain a brown paste mixture; raising the temperature of the reaction system to 80° C., slowly dropping deionized water into the brown paste mixture, and continuously stirring to obtain a yellow solution; S13: Add an appropriate amount of hydrogen peroxide solution to the yellow solution to reduce the unreacted potassium permanganate until the solution turns bright yellow and the reaction is complete; the product after the reaction is subjected to high-speed centrifugation, washing, and drying to obtain GO.
[0014] Further, the in-situ polymerization to prepare acrylate copolymer CSW / NS-GO comprises the following steps: The silanized CSW / NS and GO are added to a mixed solvent containing acrylic monomers, and a dispersant and an activator are added, and ultrasonic treatment is performed to uniformly disperse the silanized CSW / NS and GO in the solution to form a stable dispersion. The dispersion is heated in a water bath, and an initiator is slowly added dropwise under continuous stirring under the protection of an inert gas. After the reaction is completed, the mixture is filtered, washed, and dried to obtain an acrylate copolymerized CSW / NS-GO.
[0015] Furthermore, the acrylic monomer includes one or more of butyl acrylate, ethyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl acrylate, and dodecafluoroheptyl methacrylate.
[0016] Furthermore, the mixed solvent is N,N-dimethylformamide solution; a surfactant is also added to the mixed solvent; the surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and Tween-80.
[0017] Furthermore, the dispersant is one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, and sodium carboxymethyl cellulose.
[0018] Furthermore, the activator is an organic acid, which is used to treat the silanized CSW / NS to protonate the amino group, thereby improving its activity in the in-situ polymerization reaction and better reacting with the polymerization monomer or the surface functional group of graphene oxide, specifically one or more of formic acid, acetic acid, benzoic acid, and citric acid.
[0019] Furthermore, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, potassium persulfate, and ammonium persulfate.
[0020] In the shotcrete mix ratio, the mass ratio of silicate cement to the micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers is 1:(0.015-0.03).
[0021] Beneficial effects of the present invention: 1) After adding micro-nano aggregates, the cement hydration product becomes more compact, the content of calcium hydroxide crystals is significantly reduced, and the calcium-silicon ratio of calcium silicate hydrate gel increases. Micro-nano aggregates will be enriched at the cement interface due to their migration effect, providing a large number of nucleation sites. Micro-nano aggregates and calcium silicate hydrate form nano-center shell units, thereby optimizing the performance of calcium silicate hydrate gel and improving the density of the microstructure; 2) Micro-nano aggregates can optimize the system gradation, fill the pores in the concrete, make the internal structure of the concrete denser without affecting the compressive strength, and reduce the intrusion channels of harmful substances (such as chloride ions, sulfate ions, etc.). The polymer film formed by acrylic polymers can prevent the penetration of moisture and harmful gases to a certain extent, playing a protective role. The presence of calcium sulfate whiskers can enhance the stability of the internal structure of concrete and reduce structural damage caused by environmental factors such as dry-wet cycles and freeze-thaw cycles; 3) The calcium sulfate whiskers in the micro-nano aggregate have high strength, modulus and chemical stability. Their fibrous structure can form a reinforcing skeleton inside the concrete, bridge the hydration products at both ends of the microcracks, and cooperate with the VAE matrix interface to enhance the cohesion of the concrete, enhance the overall toughness of the material, and reduce the rebound rate of the shotcrete. DETAILED DESCRIPTION
[0022] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In this application, unless otherwise specified, all percentage contents are mass percentages.
[0023] The present invention provides a micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers, the main component of which is acrylic acid ester copolymer CSW / NS-GO, and the preparation method thereof comprises the following steps: (1) Nano-silicon dioxide loaded on the surface of calcium sulfate whiskers: The calcium sulfate whisker is uniformly dispersed in anhydrous ethanol and ultrasonically treated for 0.5-1h to form a stable suspension, wherein the mass fraction of the calcium sulfate whisker is 5-10wt%. TEOS is added to the suspension to dissolve, wherein the mass ratio of the calcium sulfate whisker to TEOS is 1:(0.2-2); after adding deionized water, an acid catalyst and an epoxy silane coupling agent, the pH value is adjusted to 2-4, the temperature is controlled to 40-80°C and stirred for 3-8h, and the molar ratio of TEOS, epoxy silane coupling agent and deionized water is 1:(0.1-0.5):(4-10) to obtain CSW / NS.
[0024] (2) Silanized modified calcium sulfate whiskers; CSW / NS was added into a 50% ethanol solution containing an aminosilane coupling agent, wherein the amount of the aminosilane coupling agent was 5% of the mass of CSW / NS, and ultrasonic treatment was performed for 1-2 hours at an ultrasonic power of 200-400 W and a frequency of 40-60 kHz, and then filtered, washed and dried to obtain the silanized CSW / NS.
[0025] (3) Preparation of graphene oxide by Hummers method: Under ice bath conditions, 2g of 5000 mesh graphite powder was added to 25ml of concentrated sulfuric acid, and 1g of sodium nitrate and 6g of potassium permanganate were added after stirring evenly. The reaction temperature was controlled not to exceed 20°C, and stirring was continued for 2h to obtain a dark green mixture; the temperature was raised to 35°C and stirring was continued for 30min. The oxidation process of graphite interlayer was positive, the structure became loose, and a brown paste mixture was obtained; 50ml of deionized water was added to the reaction system, and stirring was continued for 20min. The oxidant further reacted with the graphite to promote the hydrolysis of the graphite interlayer compound, the temperature of the reaction liquid increased, and the reaction liquid turned yellow; an appropriate amount of hydrogen peroxide solution was continued to be added dropwise to reduce the residual oxidant until the solution turned bright yellow and the reaction was completed. The hydrogen peroxide solution further oxidized the graphite to increase the oxygen-containing functional groups on its surface; the product after the reaction was subjected to high-speed centrifugation, washed with 5% HCl and deionized water until no sulfate was detected, and dried in a 60°C vacuum drying oven to obtain GO. The obtained GO had a thickness of ≤5nm and a sheet diameter of 20μm.
[0026] (4) Preparation of acrylate copolymer CSW / NS-GO by in situ polymerization.
[0027] Silylated CSW / NS, GO, surfactant, dispersant and activator are added to a mixed solvent containing acrylic monomers, wherein the mixed solvent is a 50-75% by volume N,N-dimethylformamide solution, the amount of surfactant is 0.1-0.5% of the mass of GO, and the amount of dispersant is 0.5-1.5% of the mass of silanized CSW / NS; ultrasonic treatment is performed for 0.5-1h to uniformly disperse the silanized CSW / NS and GO in the solution to form a stable dispersion; the dispersion is heated in a water bath, continuously stirred under the protection of inert gas, and an initiator is slowly added dropwise; after the reaction is completed, the dispersion is filtered, washed and dried to obtain acrylate copolymerized CSW / NS-GO. Example
[0028] The weight mix ratio of shotcrete includes cement: coarse aggregate: fine aggregate: steel fiber: micro-nano aggregate: water reducer: accelerator: water = 1:1.5:1.5:0.02:0.015:0.01:0.05:0.4.
[0029] Among them, cement should meet the requirements of P·O 42.5 in GB 175-2023 "General Portland Cement"; coarse aggregate is 5-10mm crushed stone, fine aggregate is homemade II zone machine-made sand-medium sand, and fineness modulus (2.6-2.7); steel fiber should meet the requirements of GB / T39147-2020 "Steel Fiber for Concrete", with a diameter of 0.3-0.8mm and a length of 20-35mm; the water reducer is an early-strength high-performance water reducer, and the accelerator is an alkali-free accelerator.
[0030] In a low temperature environment (outdoor temperature -2°C, temperature inside the cave 16°C), the construction performance test results are shown in the table below.
[0031]
[0032] According to GB / T 50082-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", corresponding specimens were made and cured, and the frost resistance, water penetration resistance, sulfate erosion resistance, chloride ion penetration resistance and carbonization performance were tested respectively. The specific results are shown in the table below.
[0033]
[0034] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers, the main component of which is acrylic acid ester copolymer CSW / NS-GO, characterized in that The preparation method of the acrylic acid ester copolymer CSW / NS-GO comprises the following steps: (1) Loading nano-silica on the surface of calcium sulfate whiskers; dissolving a silicon source in an organic solvent containing calcium sulfate whiskers, adding deionized water and an acidic catalyst, and continuously stirring to generate silicic acid and ethanol; the silicic acid continues to undergo a condensation reaction to generate nano-silica, which interacts with the surface of the calcium sulfate whiskers in the reaction system to obtain CSW / NS; (2) Silanization modified CSW / NS; (3) Preparation of graphene oxide by Hummers method; (4) Preparation of acrylate copolymer CSW / NS-GO by in situ polymerization.
2. A micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 1, characterized in that In the step 1), the mass fraction of the organic solvent containing calcium sulfate whiskers is 5-10wt%, ultrasonic pretreatment is performed for 0.5-1h, and after adding deionized water and an acidic catalyst, the temperature is controlled to be 40-80°C and stirring is continued for 3-8h; the mass ratio of the calcium sulfate whiskers to the silicon source is 1:(0.2-2); the pH value of the acidic catalyst is adjusted to 2-4, and the acidic catalyst is one or more of tartaric acid, methanesulfonic acid, and p-toluenesulfonic acid; the silicon source is sodium silicate or ethyl orthosilicate.
3. A micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 2, characterized in that An epoxy silane coupling agent is further added to the mixed solution; the epoxy silane coupling agent is one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; The molar ratio of the silicon source, the epoxy silane coupling agent and the deionized water is 1:(0.1-0.5):(4-10).
4. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 1, characterized in that The method for silanization modification of CSW / NS is as follows: adding the CSW / NS to a 50% ethanol solution containing an aminosilane coupling agent, ultrasonically treating for 1-2 hours, filtering, washing, and drying to obtain the silanized CSW / NS.
5. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 4, characterized in that The amount of the aminosilane coupling agent is 5% of the mass of CSW / NS; the aminosilane coupling agent is one or more of γ-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; in the ultrasonic treatment, the ultrasonic power is 200-400W and the frequency is 40-60kHz.
6. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 1, characterized in that In step 3), the specific steps of preparing graphene oxide by the Hummers method are: S11: In an ice bath, add graphite powder to concentrated sulfuric acid, stir evenly, then add sodium nitrate and potassium permanganate, control the reaction temperature not exceeding 20°C, and continue stirring to obtain a dark green mixture; S12: transferring the dark green mixture to a warm water bath, controlling the temperature not to exceed 50° C., and continuously stirring to obtain a brown paste mixture; raising the temperature of the reaction system to 80° C., slowly dropping deionized water into the brown paste mixture, and continuously stirring to obtain a yellow solution; S13: adding an appropriate amount of hydrogen peroxide solution to the yellow solution to reduce unreacted potassium permanganate until the solution turns bright yellow and the reaction is complete; subjecting the product after the reaction to high-speed centrifugation, washing, and drying treatment to obtain graphene oxide.
7. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 1, characterized in that In the step 4), the acrylate copolymer CSW / NS-GO is prepared by in-situ polymerization, specifically, the silanized CSW / NS and GO are added to a mixed solvent containing acrylic monomers, and ultrasonic treatment is performed to uniformly disperse the silanized CSW / NS and GO in the solution to form a stable dispersion; The dispersion is heated in a water bath, continuously stirred under the protection of an inert gas, and the initiator is slowly added dropwise; after the reaction is completed, the dispersion is filtered, washed, and dried to obtain the acrylate copolymer CSW / NS-GO.
8. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 7, characterized in that The acrylic monomer includes one or more of butyl acrylate, ethyl acrylate, methyl methacrylate, hydroxyethyl methacrylate, glycidyl methacrylate, isooctyl acrylate, hydroxyethyl acrylate, and dodecafluoroheptyl methacrylate; the initiator is one or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, potassium persulfate, and ammonium persulfate.
9. The micro-nano aggregate based on in-situ polymerization of silanized calcium sulfate whiskers according to claim 7, characterized in that The mixed solvent includes N,N-dimethylformamide, a surfactant, a dispersant, an activator and water; the volume fraction of the N,N-dimethylformamide solution is 50-75%; the amount of the surfactant is 0.1-0.5% of the mass of GO; the amount of the dispersant is 0.5-1.5% of the mass of the silanized CSW / NS; The surfactant is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and Tween-80; The dispersant is one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, and sodium carboxymethyl cellulose; The activator is one or more of formic acid, acetic acid, benzoic acid and citric acid.
10. The use of any one of claims 1 to 9 based on the in-situ polymerization of silanized calcium sulfate whiskers as a micro-nano aggregate, characterized in that In the shotcrete mix ratio, the mass ratio of silicate cement to the micro-nano aggregate is 1:(0.015-0.03).
Citation Information
Cited By
High-toughness solid-waste-based 3D printing material and preparation process
CN121021109A
High-toughness solid waste-based 3D printing material and preparation process
CN121021109B